ChemInform Abstract: Polycationic Ligands in Gold Catalysis: Synthesis and Applications of Extremely π‐Acidic Catalysts. Issue 27 (8th July 2014) - Carreras, Javier; Gopakumar, Gopinadhanpillai; Gu, Lianghu; Gimeno, Ana; Linowski, Pawel; Petuskova, Jekaterina; Thiel, Walter; Alcarazo, Manuel
Abstract Application of this method is exemplarily demonstrated by the synthesis of Marylaurencinol A (IX).